Pengembangan Modul Stock Fulfillment Online Transaction pada Aplikasi Distribution Center System menggunakan Framework Flask di PT.XYZ - Ogotan, Tifano Eng; David, Felix (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The rapid advancement of information technology necessitates that every business adapts to keep pace with technological developments. PT. XYZ, a retail and distribution company, faced challenges with their outdated technology, specifically Oracle Forms. Oracle Forms incurred high maintenance costs and was limited to running on legacy systems. Consequently, PT.XYZ decided to create a Stock Fulfillment Online Transaction module using the Flask frameworks and Python. The development process followed the Agile Scrum methodology, including stages such as requirement analysis, sprint planning, iterative development, continuous testing, and final evaluation. The outcome of this application development demonstrates that using Flask frameworks and Python allows for an application that can operate across various platforms while reducing maintenance costs.